Obraz wartości PRL w komiksie Henryka Jerzego Chmielewskiego Tytus, Romek i A’Tomek (analiza ksiąg z lat 1966–1987) - Grzegorzewski, Krzysztof (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2018)
Author analyses a popular comic book series by H.J. Chmielewski, Tytus, Romek & A’Tomek (book from 1966–1987) and tries to reconstruct a propagandist vision of the Polish Peoples Republic’s reality. The main research tool is a content analysis of book, using knowledge of the political history of Poland and the world (1945–1989), social and mass communication context, history of media in Poland and rhetorics. Author describes the results, in relation to book by sociologist, Hanna Świda-Ziemba: The youth of Polish People’s Republic.